Portugal : 2012 Article IV Consultation and Sixth Review Under the Extended Arrangement and Request for Waivers of Applicability of End-December Performance Criteria-Staff Reports;. (IMF Staff Country Reports; Country Report ;, 2013)
Mounting funding pressures has tipped Portugal into an acute economic crisis in 2011. The roots of the crisis could be traced to Portugal's failure to adapt to the rigors of monetary union. With economic institutions, policies, and incentives ill-adapted to the opportunities, Portugal's external stability risks also rose gradually. However, the current account has improved substantially with financial imbalances being corrected across private and public sectors. Fiscal adjustment also made substantial progress, while structural reforms have been progressing.